Skills and competencies that a new ENT specialty trainee year 3 should possess: a live Delphi study. Issue 2 (9th February 2023) - Rocke, J; Heward, E; Stapleton, E
Abstract: Objective: The aim of this study was to develop a novel live Delphi method to obtain a consensus on the skills and competencies that a new ENT registrar (specialty trainee level 3) should possess. Developing a clear outcome set for core surgical trainees is important so that this phase of training can be directed at specific aims. Method: Attendees at the North of England meeting participated in this Delphi exercise. Participants comprised a range of ENT professionals from medical student to consultant surgeons. The main outcome measure of consensus was defined prior to the study as the median response value: strongly agree or more for positive consensus and strongly disagree or less for negative consensus. Results: This study identified multiple areas that reached consensus relating to elective and operative skills and demonstrated agreement in areas relating to ENT specific and allied specialty experience. Conclusion: This study has highlighted a novel method for shaping surgical curricula.